Copper-based molecular sieve catalyst, preparation method thereof and application of copper-based molecular sieve catalyst in selective reduction of NOx

By adjusting the preparation process of the copper-based molecular sieve catalyst, optimizing the Cu ion active site of the catalyst, the problem of high N2O generation in the prior art is solved, and efficient NOx conversion and low N2O generation are achieved.

CN119608231AActive Publication Date: 2025-03-14SHANGHAI JIAOTONG UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411832929.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The amount of N2O generated by existing copper-based molecular sieve catalysts during NOx post-treatment is high, which affects the efficiency of the SCR catalytic system.

Method used

By adjusting the precursor Na+/TMAda+ ratio in the preparation process of SSZ-13 molecular sieve, the number of paired aluminum sites in the silicon-aluminum framework of the molecular sieve is controlled, and the Cu loading on the catalyst surface is controlled by regulating the copper ion solution concentration, thereby optimizing the binding strength and reaction activity of the Cu ion active sites of the catalyst.

Benefits of technology

It is achieved to effectively inhibit the formation of N2O while maintaining a high NOx conversion rate, and the catalyst has good water and sulfur resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608231A_ABST
    Figure CN119608231A_ABST
Patent Text Reader

Abstract

The invention provides a copper-based molecular sieve catalyst, a preparation method thereof and application of the copper-based molecular sieve catalyst in selective reduction of NOx, and belongs to the technical field of molecular sieves. Cu ion active sites on the surface of the catalyst can be regulated and optimized by adjusting the proportion of a precursor guiding agent Na < + > / TMADa < + > in the preparation process of the SSZ-13 molecular sieve and the Cu loading capacity in the preparation process of the Cu / SSZ-13 catalyst, so that the NH3-SCR copper-based molecular sieve catalyst capable of highly selectively reducing NOx is prepared; and the generation of N2O in the tail gas of the diesel engine can be effectively inhibited while the high NOx conversion rate is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of molecular sieves, and in particular to a copper-based molecular sieve catalyst and a preparation method thereof and a method for selectively reducing NO x Application in. Background Art

[0002] In all the NO x Among the emissions, nitrous oxide (N 2 O) has received more and more attention as a new type of special pollutant in recent years. 2 O is a much stronger 2 A strong greenhouse gas, its effect is greater than that of CO 2 In addition, due to its very stable structure, it can remain in the atmosphere for more than 150 years and diffuse into the stratosphere to destroy the atmospheric ozone layer. It is considered to be the most important stratospheric ozone depleting substance in the 21st century.

[0003] For diesel engines currently used in heavy trucks and cargo ships, based on NH 3 -The SCR reactor in the SCR reaction process is a necessary NO x Aftertreatment device. With the vanadium-based catalyst (V 2 O 5 ) is prone to poisoning and deactivation at high temperatures. The copper-based molecular sieve catalyst (Cu / SSZ-13) with stronger low-temperature activity, stronger hydrothermal stability, wider effective catalytic temperature range and more economical and practical has gradually become the main NO control catalyst for vehicles and ships. x Emissions after-treatment catalyst.

[0004] Studies have shown that Cu-based catalysts have excellent SCR activity at 300°C, reaching a conversion rate of more than 90%, and maintaining a high conversion rate at 300-500°C. However, due to the special structure of the Cu active center, x During post-treatment, the N 2 O production is the highest, which is higher than the existing vanadium-based catalysts and iron-based molecular sieve catalysts. Therefore, one of the main problems of the current SCR catalytic system is to reduce N 2 The generation of O. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a copper-based molecular sieve catalyst and a preparation method thereof and a method for selectively reducing NO x The copper-based molecular sieve catalyst provided by the present invention can be used to maintain high NO x conversion rate while effectively inhibiting N 2 O is generated.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a copper-based molecular sieve catalyst, comprising the following steps:

[0008] Mix TMAdaOH, aluminum source, NaOH and water to obtain a premixed solution;

[0009] adding a silicon source to the premixed solution to form a gel solution;

[0010] The gel solution is subjected to a hydrothermal treatment and a first calcination in sequence to obtain a Na-type SSZ-13 molecular sieve;

[0011] The Na-type SSZ-13 molecular sieve is mixed with an ammonium salt solution to perform a first ion exchange to obtain NH 4 + Type SSZ-13 molecular sieve;

[0012] The NH 4 + The SSZ-13 molecular sieve is mixed with a soluble copper salt solution, and a second ion exchange and a second calcination are performed in sequence to obtain a copper-based molecular sieve catalyst;

[0013] In terms of molar amount, the Na + :TMAda + =0~1:1;

[0014] In terms of molar amount, the Si / Al ratio of the gel in the gel solution is 5 to 20:1, (Na + +TMA + ) / Si=0.5.

[0015] Preferably, the aluminum source is Al(OH) 3 , the silicon source is silica sol.

[0016] Preferably, the temperature of the gel solution forming process is 10-40° C. and the time is 0.5-3 h.

[0017] Preferably, the temperature of the hydrothermal treatment is 160-200°C and the time is 48-96h;

[0018] The temperature of the first calcination is 450-550° C., and the time is 8-10 hours.

[0019] Preferably, the concentration of the ammonium salt solution is 1 mol / L;

[0020] The temperature of the first ion exchange is 70-80° C., and the time is 12-16 hours.

[0021] Preferably, the concentration of the soluble copper salt is 0.5-1.5 mol / L.

[0022] Preferably, the temperature of the second ion exchange is 70-80°C and the time is 6-8h;

[0023] The second calcination temperature is 450-550° C. and the time is 4-6 hours.

[0024] Preferably, after the second calcination, the obtained copper-based molecular sieve catalyst is subjected to a hydrothermal aging treatment;

[0025] The temperature of the hydrothermal aging treatment is 750-850° C., and the time is 8-12 hours.

[0026] The invention provides a copper-based molecular sieve catalyst prepared by the preparation method, comprising an SSZ-13 molecular sieve and Cu loaded on the surface and internal pores of the SSZ-13 molecular sieve.

[0027] Preferably, the Cu loading in the copper-based molecular sieve catalyst is 0.5-1.5 wt%.

[0028] The present invention provides the above copper-based molecular sieve catalyst for selectively reducing NO x Application in.

[0029] The invention provides a preparation method of a copper-based molecular sieve catalyst (abbreviated as Cu / SSZ-13), comprising the following steps: mixing TMAdaOH, an aluminum source, NaOH and water to obtain a premixed solution; adding a silicon source to the premixed solution to form a gel solution; subjecting the gel solution to a hydrothermal treatment and a first calcination in sequence to obtain a Na-type SSZ-13 molecular sieve; mixing the Na-type SSZ-13 molecular sieve with an ammonium salt solution, performing a first ion exchange, and obtaining NH 4 + Type SSZ-13 molecular sieve; the NH 4 + The SSZ-13 molecular sieve is mixed with a soluble copper salt solution, and the second ion exchange and the second calcination are carried out in sequence to obtain a copper-based molecular sieve catalyst. There are paired Al sites in the SSZ-13 molecular sieve, which are mainly distributed in different skeleton structures of the molecular sieve. Keeping the silicon-aluminum ratio of the SSZ-13 molecular sieve unchanged, increasing the precursor Na + The ion concentration will increase the density of paired Al in the molecular sieve framework and most of the increased paired aluminum is distributed in the framework structure. The increase of paired Al in the framework structure will promote the stable Cu during ion exchange. 2+ The present invention adjusts the precursor directing agent Na in the preparation process of SSZ-13 molecular sieve to form an active center. + / TMA+ The ratio can control the number of paired aluminum sites in the molecular sieve silicon-aluminum framework that binds to Cu ions; the Cu loading on the molecular sieve is controlled by adjusting the concentration of the copper ion solution, and then the binding strength and reaction activity of the Cu ion active sites on the catalyst surface are regulated and optimized, thereby preparing a catalyst that can highly selectively reduce NO x NH 3 -SCR copper-based molecular sieve catalyst can maintain high NO x conversion rate and effectively inhibit the N 2 O is generated, and has good water and sulfur resistance. The results of the embodiment show that the Cu / SSZ-13 catalyst provided by the present invention has good water and sulfur resistance at 250°C. x The conversion rate is 100%, N 2 O generation is 33.7ppm; at 450℃, NO x The conversion rate was 89.3%, N 2 The amount of O generated was 21.9 ppm. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a structural schematic diagram of a catalyst performance testing system;

[0031] Figure 2 The preparation flow chart of Cu / SSZ-13 catalyst in Example 1 is as follows;

[0032] Figure 3 is the NO of different catalysts in Test Example 1 x Conversion rate;

[0033] Figure 4 is the N of different catalysts in Test Example 1 2 O generation;

[0034] Figure 5 XPS Cu 2p spectra of different catalysts in Test Example 1;

[0035] Figure 6 is the NO of different catalysts in Test Example 2 x Conversion rate;

[0036] Figure 7 is the N of different catalysts in Test Example 2 2 O generation;

[0037] Figure 8 is the NO of the catalyst of Example 1 in Test Example 3 x Conversion rate;

[0038] Fig. 9 N is the catalyst of Example 1 in Test Example 3 2 O generation;

[0039] Fig.10 At 250℃, H 2 O and SO 2 Effect on the performance of Cu / SSZ-13 (2.5 / 2.5) catalyst. DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing a copper-based molecular sieve catalyst, comprising the following steps:

[0041] Mix TMAdaOH, aluminum source, NaOH and water to obtain a premixed solution;

[0042] adding a silicon source to the premixed solution to form a gel solution;

[0043] The gel solution is subjected to a hydrothermal treatment and a first calcination in sequence to obtain a Na-type SSZ-13 molecular sieve;

[0044] The Na-type SSZ-13 molecular sieve is mixed with an ammonium salt solution to perform a first ion exchange to obtain NH 4 + Type SSZ-13 molecular sieve;

[0045] The NH 4 + The SSZ-13 molecular sieve is mixed with a soluble copper salt solution, and a second ion exchange and a second calcination are performed in sequence to obtain a copper-based molecular sieve catalyst.

[0046] Unless otherwise specified, the raw materials used in the present invention are all commercially available.

[0047] In the present invention, TMAdaOH (N,N-trimethyl-1-adamantanammonium hydroxide), an aluminum source, NaOH and water are mixed to obtain a premixed solution. In the present invention, the aluminum source is preferably Al(OH) 3 , the water is preferably deionized water. In the present invention, the NaOH is preferably added in the form of an aqueous solution, and the concentration of the NaOH aqueous solution is preferably 20wt%.

[0048] In the present invention, the mixing is preferably carried out by stirring at room temperature. In the present invention, the mixing time is preferably 20 minutes.

[0049] In the present invention, based on molar amount, Na in the premixed solution + :TMAda + =0~1:1, preferably, Na + :TMAda + =0.5~1:1; (Na + +TMA +) / Si=0.5.

[0050] Add the silicon source to the premixed solution to form a gel solution. In the present invention, the silicon source is preferably silica sol. As a specific embodiment of the present invention, the silicon source is Ludox AS-40, purchased from Sigma-Aldrich. In the present invention, the silicon source is preferably added dropwise to the premixed solution.

[0051] In the present invention, the gel solution forming process is preferably carried out under stirring conditions. In the present invention, the gel forming temperature is preferably 10-40°C, more preferably room temperature, and the time is preferably 0.5-3h, more preferably 2h.

[0052] In the present invention, the Si / Al ratio of the gel in the gel solution is preferably 5 to 20:1, more preferably 15:1, based on molar amount. + +TMA + ) / Si=0.5. As a specific embodiment of the present invention, the composition of the gel is expressed in molar amounts as ANaOH: (0.5-A)TMAdaOH: 0.033Al 2 O 3 :1SiO 2 :44H 2 O, where A values ​​are 0.25, 0.1 and 0.

[0053] After obtaining the gel solution, the present invention sequentially performs hydrothermal treatment and a first calcination on the gel solution to obtain a Na-type SSZ-13 molecular sieve. In the present invention, the hydrothermal reaction is preferably carried out in a rotating hydrothermal reactor. In the present invention, the temperature of the hydrothermal treatment is preferably 160 to 200°C, more preferably 180°C, and the time is preferably 48 to 96h, more preferably 72 to 96h. In the present invention, a Na-type SSZ-13 molecular sieve molecular sieve skeleton structure will be formed during the hydrothermal treatment.

[0054] After the hydrothermal treatment, the present invention preferably performs solid-liquid separation on the hydrothermal reaction system, and washes and dries the solid. In the present invention, the solid-liquid separation is preferably suction filtration, the washing is preferably water washing, and the number of washings is preferably 2 to 3 times. In the present invention, the drying is preferably oven drying, the drying temperature is preferably 100°C, and the drying time is preferably 12 hours.

[0055] In the present invention, the first calcination is preferably carried out in a muffle furnace, and the atmosphere of the first calcination is preferably air; the temperature of the first calcination is preferably 450-550°C, more preferably 550°C, and the time is preferably 8-10h, more preferably 10h; in the present invention, the heating rate to the first calcination temperature is preferably 1°C / min. In the present invention, the framework structure of the Na-type SSZ-13 molecular sieve will be more stable during the first calcination.

[0056] After obtaining the Na-type SSZ-13 molecular sieve, the present invention mixes the Na-type SSZ-13 molecular sieve with an ammonium salt solution to perform a first ion exchange to obtain NH 4 + In the present invention, the ammonium salt is preferably NH 4 In the present invention, the concentration of the ammonium salt solution is preferably 1 mol / L.

[0057] In the present invention, the temperature of the first ion exchange is preferably 70-80°C, and the time is preferably 12-16 hours. The present invention converts the Na-type SSZ-13 molecular sieve into NH 4 + type.

[0058] In the present invention, after the first ion exchange, the present invention preferably performs solid-liquid separation on the obtained first ion exchange system, washes and dries the obtained solid, and obtains NH 4 + Type SSZ-13 molecular sieve solid. In the present invention, the solid-liquid separation is preferably suction filtration. The present invention has no special requirements for the washing and drying, and the washing and drying methods well known in the art can be used.

[0059] Get the NH 4 + After the SSZ-13 molecular sieve, the present invention converts the NH 4 + The SSZ-13 molecular sieve is mixed with a soluble copper salt solution, and a second ion exchange and a second calcination are performed in sequence to obtain a copper-based molecular sieve catalyst. In the present invention, the soluble copper salt is preferably copper nitrate. In the present invention, the concentration of the soluble copper salt is preferably 0.5 to 1.5 mol / L, more preferably 1 mol / L.

[0060] In the present invention, the second ion exchange is preferably carried out under stirring. In the present invention, the temperature of the second ion exchange is preferably 70 to 80°C, and the time is preferably 6 to 8 hours. 2+ Loaded on the surface and internal pores of the molecular sieve.

[0061] The present invention preferably performs the second calcination in a muffle furnace, and the atmosphere of the second calcination is preferably air. In the present invention, the temperature of the second calcination is preferably 450-550°C, more preferably 500°C; the time is preferably 4-6 hours; the heating rate to the second calcination temperature is preferably 1°C / min. 2+ It will combine with the molecular sieve framework to form Cu-SSZ-13 molecular sieve.

[0062] After the second calcination, the present invention also preferably includes a hydrothermal aging treatment of the obtained copper-based molecular sieve catalyst. In the present invention, the temperature of the hydrothermal aging treatment is preferably 750 to 850°C, more preferably 800°C, and the time is preferably 8 to 12 hours, more preferably 10 to 12 hours. The present invention further improves the catalytic performance of the copper-based molecular sieve catalyst through the hydrothermal aging treatment.

[0063] After the second calcination, the present invention preferably tablets, grinds, sieves and granulates the copper-based molecular sieve catalyst. The present invention has no special requirements for the above operations, and tablets, grinds, sieves and granulates processes well known in the art can be used.

[0064] The present invention provides a copper-based molecular sieve catalyst prepared by the above preparation method, comprising SSZ-13 molecular sieve and Cu loaded on the surface and internal pores of the SSZ-13 molecular sieve, wherein the Cu is preferably Cu 2+ and Cu + In the present invention, the Cu loading in the copper-based molecular sieve catalyst is preferably 0.5-1.5wt%, more preferably 1wt%. In the present invention, the particle size of the copper-based molecular sieve catalyst is preferably 0.02-0.1μm, and the specific surface area is preferably 100-500m 2 / g, total pore volume 0.1~0.3cm 3 / g, average pore size

[0065] The present invention provides the above copper-based molecular sieve catalyst for selectively reducing NO x In the present invention, the selective reduction of NO x Preferred for selective reduction of NO in diesel engine exhaust x .

[0066] In the present invention, the application method preferably comprises the following steps:

[0067] The reaction gas is introduced into the copper-based molecular sieve catalyst to carry out a reduction reaction.

[0068] In the present invention, the composition of the reaction gas preferably includes 0.01-0.1% NO, 0.01-0.1% NH 3 1~10% O 2 and the balance gas N 2 .

[0069] In the present invention, the reaction space velocity of the reaction gas is preferably 10000 to 60000 mL·g -1 ·h -1 In the present invention, the temperature of the reduction reaction is preferably 200 to 400°C.

[0070] The copper-based molecular sieve catalyst provided by the present invention and its preparation method and its application in the selective reduction of NO are described below in conjunction with the embodiments. x The applications in the present invention are described in detail, but they should not be understood as limiting the scope of protection of the present invention.

[0071] In the following embodiments and test examples, the catalyst performance test system is mainly composed of three parts: a gas path control module, a catalytic reaction module and a gas concentration detection module. Figure 1 shown.

[0072] In the gas control module, the standard cylinder provides O 2 、N 2 、N 2 O, NO, NH 3 The gases required for the reaction are controlled by a precisely calibrated mass flow meter to control the flow of each branch gas path. When conducting a catalyst water resistance test, distilled water is heated in a constant temperature water bath to generate water vapor, and the water vapor content is determined based on the heating temperature and gas flow rate. In addition, to prevent water vapor from condensing in the pipeline, the air intake pipeline is wrapped with a heating tape for heating.

[0073] The catalytic reaction module mainly consists of two parts: a programmed temperature tubular heating furnace and a quartz tube reactor. Before the pretreatment experiment begins, fill the catalyst into the quartz tube reactor and use quartz wool to block both ends of the catalyst to prevent the catalyst from being blown into the subsequent gas pool and affecting the measurement results. The catalyst needs to be pretreated before the gas reaction officially begins. The pretreatment must be carried out in a pure nitrogen flow, so N 2 The air in the pipe is discharged by the gas control valve, and the temperature of the heating furnace is raised to 500°C and maintained at this temperature for 60 minutes. After the pretreatment is completed and the temperature of the heating furnace drops to room temperature, the performance test experiment is started. The temperature range of the performance test is between 50°C and 600°C, the heating rate is 5°C / min, and each sampling point is maintained for 10 minutes to ensure that the reaction reaches a steady state.

[0074] The gas concentration detection module mainly consists of two parts: Fourier transform infrared spectrometer and computer analysis software. The gas components measured by the test equipment have been accurately calibrated with the corresponding standard gas cylinders. In the experiment, the reaction gas concentration can be viewed in real time through the computer-specific detection software connected to the test equipment.

[0075] The catalytic performance of the catalyst is shown by the NO conversion rate, N 2 O decomposition / reduction efficiency and N 2 O selectivity is the main indicator, and the calculation formula is shown in Formula 1 to Formula 3:

[0076] NO conversion=([NO] in -[NO] out ) / [NO] in ×100% Formula 1;

[0077] N 2 O conversion=([N 2 O] in -[N 2 O] out ) / [N 2 O] in ×100% Formula 2;

[0078] N 2 O selectivity=([N 2 O] out / [NO] in )×100% Formula 3.

[0079] In formula 1 to formula 3, [NO] in and [NO] out are the NO volume concentrations at the reactor inlet and outlet, [N 2 O] in and [N 2 O] out is the reactor outlet N 2 The volume concentration of O.

[0080] The following examples and test examples are used to measure the Cu loading in the copper-based molecular sieve catalyst by inductively coupled plasma emission spectrometry (ICP).

[0081] Example 1

[0082] according to Figure 2 Preparation flow chart, preparing copper-based molecular sieve catalyst, the method is as follows:

[0083] First, 52.83 g of TMAdaOH was mixed with 20 g of deionized water, and then 5.15 g of Al(OH) was slowly added. 310.0 g of 20 wt% NaOH aqueous solution was added dropwise and stirred at room temperature for 20 min. Then 150.00 g of silicon source LudoxAS-40 was slowly added and further homogenized and stirred for 2 hours to obtain ANaOH: (0.5-A)TMAdaOH: 0.033Al 2 O 3 :1SiO 2 :44H 2 O, wherein the A value is 0.25.

[0084] After obtaining the gel solution, it was placed in a reactor and rotated at 180°C at a rate of 40 rpm for 96 hours of hydrothermal treatment. The obtained sample was then filtered, washed 3 times and precipitated to finally obtain the synthesized Na-type SSZ-13 molecular sieve precursor. It was then placed in an oven and dried at 100°C for 12 hours, and finally placed in a muffle furnace for high-temperature calcination at 550°C for 10 hours at a heating rate of 1°C / min to obtain the Na-type SSZ-13 molecular sieve. + / TMA + The ratio was named Na-SSZ-13 (2.5 / 2.5).

[0085] After the Na-type SSZ-13 molecular sieve is prepared, it is placed in 1 mol / LNH 4 Cl solution, ion exchange at 80 ° C for 12 h to obtain NH 4 + Type SSZ-13 molecular sieve, will get NH 4 + SSZ-13 molecular sieve is filtered, washed and dried.

[0086] Take 100mL of 1mol / L Cu(NO 3 ) 2 6H 2 O solution, NH 4 + The SSZ-13 molecular sieve powder was placed in a solution and stirred at 80°C in a magnetic stirring water bath for 6 h. The obtained mixture was filtered and washed 3 times, then placed in an oven at 100°C for 12 h. Finally, the dried sample was placed in a muffle furnace and calcined at 550°C for 4 h with a heating rate of 1°C / min to obtain a copper-based molecular sieve catalyst with a Cu loading of 1 wt%, recorded as Cu / SSZ-13 (2.5 / 2.5).

[0087] Test Example 1 Different Na + / TMA + Effect of Cu / SSZ-13 catalyst ratio on SCR performance and N 2 Effect of O generation

[0088] According to the method of Example 1, a Cu loading of 1 wt % and Na + / TMA + The ratios of Cu / SSZ-13 catalysts are 0 / 5, 1 / 4, and 2.5 / 2.5, respectively. Fresh and hydrothermally aged (800°C, 12h hydrothermal aging treatment) are denoted as Cu / SSZ-13(0 / 5)Fresh, Cu / SSZ-13(1 / 4)Fresh, Cu / SSZ-13(2.5 / 2.5)Fresh (i.e., Example 1), Cu / SSZ-13(0 / 5)Aged, Cu / SSZ-13(1 / 4)Aged, and Cu / SSZ-13(2.5 / 2.5)Aged. The difference between Cu / SSZ-13(0 / 5) and Example 1 is that the amount of NaOH aqueous solution added is 0;

[0089] The difference between Cu / SSZ-13 (1 / 4) and Example 1 is that the amount of NaOH aqueous solution added is 4.0 g.

[0090] Determination of the above catalysts for NO x NH 3 - Standard SCR reaction catalytic activity and N in SCR process 2 O production. Reaction space velocity 60000mL·g -1 ·h -1 The reaction inlet gas conditions are 1000ppm NO, 1000ppm NH 3 , 10% O 2 and the balance gas N 2 .

[0091] NO of different catalysts x Conversion rate Figure 3 As shown, N 2 O production Figure 4 As shown. Figure 3 , Figure 4 It can be seen that at 60000mL·g -1 ·h -1 All fresh Cu / SSZ-13 molecular sieve catalysts showed high NO x The NO conversion efficiency of Cu / SSZ-13(0 / 5) and Cu / SSZ-13(1 / 4) catalysts is better than that of Cu / SSZ-13(2.5 / 2.5) at temperatures below 200°C. However, when the temperature continues to rise to above 400°C, the NO conversion efficiency of Cu / SSZ-13(0 / 5) and Cu / SSZ-13(1 / 4) catalysts is higher than that of Cu / SSZ-13(2.5 / 2.5). 3 Non-selective oxidation of NO xThe conversion rates all decreased to varying degrees. Among them, the conversion efficiency of the Cu / SSZ-13 (2.5 / 2.5) catalyst decreased the least and maintained a high conversion efficiency of more than 80%. In comparison, the activity of the Cu / SSZ-13 (0 / 5) and Cu / SSZ-13 (1 / 4) catalysts decreased significantly, especially the activity of Cu / SSZ-13 (0 / 5), which decreased by nearly 50%.

[0092] After hydrothermal treatment at 800°C, the three catalysts showed more obvious differences in high-temperature activity: the aged Cu / SSZ-13 (2.5 / 2.5) catalyst showed better catalytic performance than the aged Cu / SSZ-13 (0 / 5) and Cu / SSZ-13 (1 / 4) catalysts in almost the entire temperature range.

[0093] The XPSCu 2p spectra of Cu / SSZ-13(0 / 5)Fresh, Cu / SSZ-13(1 / 4)Fresh, and Cu / SSZ-13(2.5 / 2.5)Fresh are as follows Figure 5 As shown. Figure 5 As shown in the figure, Cu2p can be divided into two main peaks (Cu 2p1 / 2 and Cu 2p3 / 2) and one satellite peak (Sat.). There are two Cu active center site peaks in the Cu 2p2 / 3 orbital, located in the binding energy range of 934.8-936.2eV and 933.5eV respectively. 2+ The binding energy of the peak is about 935.5 eV, and the isolated Cu, CuO and Cu 2 The peak binding energy of O is around 933.5 eV. When the Cu loading is less than 3%, there is no CuO on the surface of the molecular sieve, only Cu(OH) + Cu 2+ Therefore, the characteristic peak on the Cu 2p2 / 3 orbital corresponds to Cu 2+ And the intensity peak of isolated Cu. According to the Cu 2p2 / 3 orbital spectra of the three molecular sieves, Cu 2+ active center, and Cu / SSZ-13 (2.5 / 2.5) Cu 2+ The orbital peak area is significantly larger than that of the other two catalysts.

[0094] Further study of Cu in the three catalysts 2+ The content distribution of isolated Cu was also investigated. The two deconvoluted Cu forms at Cu 2p2 / 3 were semi-quantitatively calculated. The peak areas of the two forms were calculated by Gaussian function and compared. The Cu distribution of different catalysts was obtained. 2+ and Cu +The proportion of the catalysts is shown in Table 1. 2+ The ratio of Na + / TMA + and reached a maximum value of 29.6% at a ratio of 1:1, which was higher than that of TMA alone. + Cu / SSZ-13(0 / 5) synthesized as an inorganic directing agent 2+ The ratio increased by nearly one-fold, indicating that by adjusting the Na + / TMA + The ratio of can effectively affect the Al paired The number of sites and the Cu after ion exchange 2+ The number of active sites can effectively reduce the N 2 The amount of O produced.

[0095] Table 1 Cu in different Cu / SSZ-13 catalysts 2+ And the content distribution of isolated Cu

[0096] Cu / SSZ-13(0 / 5)Fresh Cu / SSZ-13(1 / 4)Fresh Cu / SSZ-13(2.5 / 2.5)Fresh <![CDATA[Cu 2+ Ion]]> 14.6% 19.5% 29.6% <![CDATA[Cu + Ion]]> 85.4% 80.5% 70.4%

[0097] The specific surface area, total pore volume and average pore size of different Cu / SSZ-13 catalysts are shown in Table 2.

[0098] Table 2 Specific surface area, total pore volume and average pore diameter of different Cu / SSZ-13 catalysts

[0099]

[0100] Test Example 2 Effect of Different Cu Loadings on SCR Performance and N of Cu / SSZ-13 Catalyst 2 Effect of O generation

[0101] According to the above method, Na + / TMA + The Cu / SSZ-13 catalysts with a ratio of 2.5 / 2.5 and Cu loadings of 0.5 wt%, 1 wt%, and 1.5 wt% are respectively denoted as Cu 0.5 / SSZ-13 (2.5 / 2.5), Cu / SSZ-13 (2.5 / 2.5) (Example 1) and Cu 1.5 / SSZ-13(2.5 / 2.5). Among them, Cu 0.5 / SSZ-13 (2.5 / 2.5) is different from Example 1 in that Cu(NO 3 ) 2 6H 2 The concentration of O solution is 0.5 mol / L, Cu1.5 / SSZ-13 (2.5 / 2.5) is different from Example 1 in that Cu(NO 3 ) 2 6H 2 The concentration of O solution is 1.5 mol / L.

[0102] Determination of the catalyst for NO x NH 3 Standard SCR reaction catalytic activity and N in SCR process 2 O production. Reaction space velocity 60000mL·g -1 ·h -1 The reaction inlet gas conditions are 1000ppm NO, 1000ppm NH 3 , 10% O 2 and the balance gas N 2 .

[0103] NO of different catalysts x Conversion rate Figure 6 As shown, N 2 O production Figure 7 As shown. Figure 6 , Figure 7 It can be seen that when the Cu loading is less than 1wt%, the low-temperature activity of the Cu / SSZ-13 (2.5 / 2.5) catalyst is poor, and the high-activity temperature range is shifted backward, and the conversion rate can only reach more than 90% at around 350°C. As the Cu loading increases, when the Cu loading exceeds 1wt%, the overall low-temperature activity of the catalyst is greatly improved, and the conversion rate can reach more than 90% at around 225°C and maintain a high conversion rate to above 500°C. However, when the Cu loading exceeds 1wt%, the high-temperature activity of the Cu / SSZ-13 (2.5 / 2.5) catalyst after 400°C decreases to a certain extent. When the temperature reaches 550°C, the NO conversion rate of the Cu / SSZ-13 (2.5 / 2.5) catalyst is 87%, while the Cu 1.5 / SSZ-13 (2.5 / 2.5) catalyst dropped to 79%. 0.5 / SSZ-13 (2.5 / 2.5) catalyst has the highest NO x The N conversion rate of Cu / SSZ-13 (2.5 / 2.5) catalysts with different Cu loadings in the SCR process was further investigated. 2 O generation, it was found that Cu / SSZ-13 (2.5 / 2.5) catalyst had a significant N 2 The amount of O generated increases with the increase of Cu loading. However, when the Cu loading is less than 1wt%, Cu 0.5 / SSZ-13 (2.5 / 2.5) catalyst hardly generates N at low temperature (below 300℃)2 O.

[0104] NO generation over different Cu / SSZ-13 catalysts at 250℃ and 450℃ x Conversion rate and N 2 The amount of O generated is shown in Table 3.

[0105] Table 3 NO generation over different Cu / SSZ-13 catalysts at 250℃ and 450℃ x Conversion rate and N 2 O production

[0106]

[0107] It can be seen from Table 3 that the NO x The conversion rate is the highest, reaching 100% (N 2 O generated 33.7ppm), when the temperature rises to 450℃, NO x The conversion rate can be maintained at 89.3% (N 2 O generation 21.9ppm); Cu 0.5 / SSZ-13(2.5 / 2.5)NO x The conversion rate is the highest at 450℃, reaching 95.7% (N 2 O generated 17.7ppm), but at a low temperature of 250℃ only 49.4% (N 2 O generation: 11.7ppm).

[0108] Test Example 3 Effect of different reaction space velocities on SCR performance and N of Cu / SSZ-13 catalyst 2 Effect of O generation

[0109] Determination of the effect of catalyst on NO in Example 1 x NH 3 - Standard SCR reaction catalytic activity and N in SCR process 2 The production of O. The reaction space velocities were 30000, 60000, and 90000 mL g -1 ·h -1 The reaction inlet gas conditions are 1000ppmNO, 1000ppmNH 3 , 10% O 2 and the balance gas N 2 .

[0110] Example 1 Catalyst NO x Conversion rate Figure 8 As shown, N 2 O production Fig. 9 As shown. Figure 8 , Fig. 9 It can be seen that as the space velocity gradually increases, the NO x The conversion efficiency gradually decreases, but it can still maintain a high conversion efficiency of more than 90% between 225 and 400°C. As the temperature increases, the efficiency of the catalyst with a higher space velocity in the experiment decreases faster.

[0111] At different space velocities, the N generated by the catalyst 2 O concentration has the same trend of change, which is to increase first, then decrease, and finally increase again with increasing temperature. x The opposite of conversion rate is that N 2 The concentration of O decreased with the increase of space velocity, and at 30000 mL·g -1 ·h -1 Under low airspeed conditions, low temperature N 2 The O concentration peak shifted to the left and appeared at around 225 °C. As the space velocity increased, the peak continued to move to higher temperatures. -1 ·h -1 The air velocity reaches about 250°C.

[0112] Test Example 4 Water and sulfur resistance of Cu / SSZ-13 catalyst

[0113] The H of the Cu / SSZ-13 (2.5 / 2.5) catalyst of Example 1 was tested at 250°C. 2 O and SO 2 Poisoning performance test experiment, where the reaction gas conditions are 1000ppm NO, 1000ppm NH 3 , 10% O 2 and balance gas N 2 , reaction space velocity is 60000ml·g -1 ·h -1 When testing water resistance and sulfur resistance, 10 vol.% H 2 O and 50 ppm SO 2 .

[0114] H at 250℃ 2 O and SO 2 Effects on the performance of Cu / SSZ-13 (2.5 / 2.5) catalysts Fig.10 As shown. Fig.10 It can be seen that under the standard SCR reaction gas conditions in the first 4 h, the performance of the Cu / SSZ-13 (2.5 / 2.5) catalyst is stable, and NO x The conversion efficiency was maintained at about 100%, and 10 vol.% H was introduced at 4.5 h. 2After O gas was introduced, the NOx conversion rate dropped significantly, from 100% to about 84% within 0.5h.

[0115] In closing H 2 After 2 hours of O gas line, open SO 2 The gas line is filled with 50 ppm SO 2 , found NO x The conversion rate of SO decreased to a certain extent, and stabilized at about 85% after 30 minutes. After closing the gas line, it was found that the SCR performance of the catalyst recovered, but did not return to the state when SO was introduced. 2 The previous 100% was only about 92%. After 2 h, the catalyst was placed in pure N 2 After desulfurization regeneration treatment at 500°C for 1 hour under atmosphere conditions and then placed back in the standard SCR gas atmosphere for experiments, it was found that its conversion rate could basically recover to 100%.

[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a copper-based molecular sieve catalyst, characterized in that: The following steps are involved: Mix TMAdaOH, aluminum source, NaOH and water to obtain a premixed solution; adding a silicon source to the premixed solution to form a gel solution; The gel solution is subjected to a hydrothermal treatment and a first calcination in sequence to obtain a Na-type SSZ-13 molecular sieve; The Na-type SSZ-13 molecular sieve is mixed with an ammonium salt solution to perform a first ion exchange to obtain NH4 + Type SSZ-13 molecular sieve; The NH4 + The SSZ-13 molecular sieve is mixed with a soluble copper salt solution, and a second ion exchange and a second calcination are performed in sequence to obtain a copper-based molecular sieve catalyst; In terms of molar amount, the Na + :TMAda + =0~1:1; In terms of molar amount, the Si / Al ratio of the gel in the gel solution is 5 to 20:1, (Na + +TMA + ) / Si=0.

5.

2. The preparation method according to claim 1, characterized in that: The aluminum source is Al(OH)3, and the silicon source is silica sol; The temperature of the gel solution forming process is 10-40° C. and the time is 0.5-3 hours.

3. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal treatment is 160-200°C and the time is 48-96h; The temperature of the first calcination is 450-550° C., and the time is 8-10 hours.

4. The preparation method according to claim 1, characterized in that: The concentration of the ammonium salt solution is 1 mol / L; The temperature of the first ion exchange is 70-80° C., and the time is 12-16 hours.

5. The preparation method according to claim 1, characterized in that: The concentration of the soluble copper salt is 0.5-1.5 mol / L.

6. The preparation method according to claim 1 or 5, characterized in that: The temperature of the second ion exchange is 70-80°C and the time is 6-8h; The second calcination temperature is 450-550° C. and the time is 4-6 hours.

7. The preparation method according to claim 1, characterized in that: After the second calcination, the obtained copper-based molecular sieve catalyst is subjected to a hydrothermal aging treatment; The temperature of the hydrothermal aging treatment is 750-850° C., and the time is 8-12 hours.

8. The copper-based molecular sieve catalyst prepared by the preparation method according to any one of claims 1 to 7, comprising SSZ-13 molecular sieve and Cu loaded on the surface and internal pores of the SSZ-13 molecular sieve.

9. The copper-based molecular sieve catalyst according to claim 8, characterized in that: The Cu loading amount in the copper-based molecular sieve catalyst is 0.5-1.5 wt %.

10. The copper-based molecular sieve catalyst according to claim 8 or 9 is used for selective reduction of NO x Application in.

Citation Information

Patent Citations

  • Catalyst and preparation thereof and method for selective catalytic reduction of NO by NH3

    CN109174167A

  • Modified Cu-SSZ-13 molecular sieves as well as preparation method and application thereof

    CN110078090A

  • Preparation method of catalyst for improving denitration performance of metal modified SSZ-13

    CN117019214A

  • MOLECULAR SIEVE Cu-SSZ-13, ITS SYNTHESIS METHOD, CATALYST AND USE THEREOF

    US20220258140A1

  • Modified copper zeolites and method of using the same for treatment of gas streams containing NOX

    WO2024211693A1